Navigating the digital financial landscape: unraveling the impact of financial behavior traits on women-owned enterprises in the new normal perspective - Serin Peter; Geetha E; Anju Gupta (Cogent Business & Management, 2024)
Exploring the financial behavior traits amidst the unexpected financial challenges and the unparalleled rise in fintech, this study provides insight into the interplay of entrepreneur digital financial literacy (EDFL), entrepreneur financial competency (EFC), and entrepreneur financial skill (EFS) impacting entrepreneur financial decision-making (EFDM). Toward this goal, data were gathered from 223 active women entrepreneurs from India who have accounts in the social media platform. The three-step hierarchical regression analysis disclosed that an entrepreneur with sound EDFL, EFS, and EFC can significantly enhance strategic decision-making (EFDM). The research outcome reveals that EFDM is a consistent predictor of the financial performance of women-owned enterprises. In addition, the entrepreneur's financial decision-making does not mediate the relationship between financial experience, financial competency, financial skill budgeting, and financial skill_acumen with financial performance. In contrast, partial mediation is observed between digital financial awareness, digital financial knowledge, and financial skill_analytics. The novel insight accounted for a significantly low level of experience in entrepreneurs' utilization of digital platforms for payment, financing loans, and asset management. The outcome carries academic, regulatory, and managerial significance, recognizing the unique interaction; the cumulative efforts strengthen the capacity to address socio-economic challenges and translate them into gender-specific policy interventions and practices.The research presents a timely exploration into the evolving financial landscape, particularly focusing on the digital literacy and competency of women entrepreneurs amidst unprecedented challenges and the rapid expansion of fintech solutions. By delving into the intricate dynamics of digital financial behavior traits, the study underscores the pivotal role of entrepreneur digital financial literacy, competency, and skill in shaping strategic decision-making processes. The findings not only highlight the indispensable link between entrepreneur financial decision-making and enterprise performance but also shed light on the nuanced relationships within the digital financial realm. This research contributes significant insights into how women entrepreneurs leverage digital platforms for financial transactions, loan management, and asset optimization, despite facing notable challenges in experience levels. Such insights hold profound implications for academia, regulatory frameworks, and managerial practices, advocating for tailored interventions and policies that empower women entrepreneurs and foster inclusive economic growth amidst the evolving financial landscape.
Keywords: B54; G40; L25; L26; 650; Financial performance; Financial digital literacy; Financial competency; Financial decision-making; Financial behavior; Women entrepreneurship; SDG 8